Identification and virulence screening of Aeromonas spp. isolated from healthy and epizootic ulcerative syndrome (EUS) - infected fish - Torres, James L.; Shariff, Mohamed; Law, A. T. (1989)
Healthy and infected fish with epizootic ulcerative syndrome (EUS) were sampled for Aeromonas detection and virulence screening. Forty-three characters, eight of which were of diagnostic value, were used to identify 54 isolated strains. When the results were compared to Bergey's Manual 1984 edition for speciation of Aeromonas, five groups were identified: A. hydrophila (24 groups were isolates); A. hydrophila-like (17 isolates); A. sobria(three isolates); A. soobria-like (four isolates); A. caviae (one isolate); and Aeromonas sp. (five isolates). The two ATCC reference cultures characterized alongside the test organism corresponded to their original identities: A. hydrophila and A. sobria. The 54 strains were prescreened for virulence by injecting juvenile grass carp (Ctenopharyngodon idella) with 0.1ml of 6.4x 10 cells/ml of the isolate. On the basis of percentage mortalities, the isolates were tentatively categorized as highly virulent (nine), weakly virulent (12), and avirulent (27) strains. All the highly virulent and weakly virulent strains belonged to the A. hydrophila group. Selective LD50 of highly virulent strains ranged from 1 to 5 x 1o. No correlation could be found in the biochemical characteristics between virulent and avirulent strains. The presence of virulence strains in healthy fish suggests the opportunistic character of the organism.